Sustainable Development Disciplines for Society Breaking Down the 5Ps-People, Planet, Prosperity, Peace, and Partnerships - Urata, Shujiro; Akao, Ken-Ichi; Washizu, Ayu (Sustainable Development Goals Series, 2023)
This multidisciplinary Open Access book provides nine problem-solving lectures for sustainable development for the planet and prosperity. Those are two of the five keywords for the Sustainable Development Goals (SDGs): people, the planet, prosperity, peace, and partnerships, or "the 5Ps". Each of these lectures is classified into one of the keywords for SDGs and based on law, economics, management, international trade, input-output analysis, or agricultural and urban engineering. Further, each lecture delineates the essence of each discipline when it is practically applied to development studies. This book, Sustainable Development Disciplines for Society, along with its sister volume related to the people, peace and partnerships, will be useful in studying development. Interdisciplinary research is necessary to achieve the SDGs advocated by the United Nations. Hence, it is essential to learn the basics of individual disciplines, as they each offer ample knowledge fostering problem solving through the accumulation of existing research. This and its sister volume are the first comprehensive textbooks summarizing the essence of each necessary discipline to approach development studies from an interdisciplinary perspective. In developing countries, this book will provide access to development research for readers aiming to further develop their own nations. Moreover, in developed countries, this book will provide access to problem-solving research for readers seeking holistic solutions to complex social problems.